The effects of environment on the intrinsic shape of galaxies - Rodríguez Moncada, Silvio Ribamar (2016)
We measure the effect of the environment on the intrinsic shapes of spiral and elliptical galaxies by finding the 3D shape distribution and dust extinction that fits better the projected shape of galaxies in different environment. We find that spiral galaxies in groups are very similar to field spirals with similar intrinsic properties (magnitudes, sizes and colours). But for spirals in groups, those in denser environments or closer to the centre of the group tend to have a more circular disc than similar galaxies in less dense environments or far from the group centres. Also we find that central spiral galaxies in their groups tend to be thinner than other similar spirals. For ellipticals, we do not find any important dependence of their shape on their position in a group or on the local density. However, we find that elliptical galaxies in groups tend to be more spherical than field ellipticals with similar intrinsic properties. We find that, once in groups, the shape of member galaxies do not depend on group mass, regardless of their morphological type.